A Hofer-Type Norm of Hamiltonian Maps on Regular Poisson Manifold - Dawei Sun; Zhenxing Zhang (Journal of Applied Mathematics)
We define a Hofer-type norm for the Hamiltonian map on regular Poisson manifold and prove that it is nondegenerate. We show that the L1,∞-norm and the L∞-norm coincide for the Hamiltonian map on closed regular Poisson manifold and give some sufficient conditions for a Hamiltonian path to be a geodesic. The norm between the Hamiltonian map and the induced Hamiltonian map on the quotient of Poisson manifold (M,{·,·}) by a compact Lie group Hamiltonian action is also compared.